Characterization of MgCo2O4 as an Electrode for High Performance Supercapacitors - Rajan, Jose; Krishnan, Syam G.; Midhun, Harilal; Baiju, Vidyadharan; Izan Izwan, Misnon; Mohd Hasbi, Ab. Rahim; Jamil, Ismail (Elsevier, 2015)
Metal cobaltites have promising electrochemical properties for their application as an energy storage medium. In this paper, usefulness of MgCo2O4 as a supercapacitor electrode is demonstrated and compared its performance with two other cobaltites, MnCo2O4 and CuCo2O4. The materials are synthesized using molten salt method and characterized by X-ray diffraction, scanning electron microscopy, BET surface area, cyclic voltammetry, galvanostatic charge–discharge cycling, and electrochemical impedance spectroscopy techniques. The MgCo2O4 electrodes show superior charge storage properties in 3 M LiOH among a diverse choice of electrolytes. The MgCo2O4 show higher theoretical (∼3122 F/g) and practically achieved capacitance (∼320 F/g), larger coulombic efficiency, and cycling stability than the other two; therefore, it could be developed as a low-cost energy storage medium.